Parents voyageurs. Croisières familiales au long cours - Anne Gaugue (EchoGéo)
This article looks at the geography of seafaring parents travelling with their children from port of call to port of call for at least a year, and often much longer.  To explain their choice of sailing with their children, the parents often put forward an openness to the world and a turning inward to the family as the main motivations.  During the cruise, these parents on the move choose the length and location of the stopovers according to what they consider as essential for their children: their schooling and the opportunity to be in contact with other children. Be it oceanic areas or tropical islets, parental supervision also varies according to the place frequented.